A Life With No Direction: New Frontiers in Psychopathology. Issue 5 (4th July 2018) - Formica, Ivan; Branca, Maria Caterina; Mento, Carmela; Di Giorgio, Antonio; Iacolino, Calogero; Pellerone, Monica
Abstract : This article will explore the new forms of psychopathology that have emerged from the view of complex thoughts. We will especially focus on the forms of life that have developed in the postmodern world, highlighting their character of fragmentation, as well as their incessantly recurrent movement. When people look at the shapes of the external world, they can draw those of their inner world, and vice versa: from the perspective of their inner world, they can describe the shapes of the external world. Finally, we propose the possibility of regaining authenticity and creativity, starting with the recreation of links with life and living environments.